Tasty total comfort : cozy recipes with a modern touch. (Clarkson Potter/Publishers, 2022)
"75 Tasty recipes for the favorite comfort food you love from cuisines around the world, with plenty of surprises and wow-factors to keep things interesting. Tasty knows that "classic" American comfort food encompasses a multitude of cuisines, flavors, and recipes from diverse cultures. Inspired by contemporary ingredients, Tasty Total Comfort brings the brand's tried and true formula--easy-to-follow, accessible recipes with exciting, entertaining spins--to nostalgic classics, including SpaghettiOs alla Vodka, Huevos Rancheros Breakfast Tostadas, Korean Hot Dogs, Purple Boba Tea, and Pigs-in-a-Blanket Pull-Apart Bread. And for dessert (preferably at every meal), all your childhood favorites, with new glow-ups--Fried Mini Oreo Bites, Spumoni Sundae Brownies, Japanese Matcha Pudding Cups, and Eid Moon Cookies--are here for you, too"--